2015
DOI: 10.3390/rs71013251
|View full text |Cite
|
Sign up to set email alerts
|

Combined Multi-Temporal Optical and Radar Parameters for Estimating LAI and Biomass in Winter Wheat Using HJ and RADARSAR-2 Data

Abstract: Leaf area index (LAI) and biomass are frequently used target variables for agricultural and ecological remote sensing applications. Ground measurements of winter wheat LAI and biomass were made from March to May 2014 in the Yangling district, Shaanxi, Northwest China. The corresponding remotely sensed data were obtained from the earth-observation satellites Huanjing (HJ) and RADARSAT-2. The objectives of this study were (1) to investigate the relationships of LAI and biomass with several optical spectral veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
98
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 51 publications
6
98
0
Order By: Relevance
“…There are three CP decomposition algorithms named m − δ decomposition, m − α decomposition and m − χ decomposition [10]. However, α is a supplementary angle for χ.…”
Section: Decomposition Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…There are three CP decomposition algorithms named m − δ decomposition, m − α decomposition and m − χ decomposition [10]. However, α is a supplementary angle for χ.…”
Section: Decomposition Parametersmentioning
confidence: 99%
“…Polarimetric decomposition is a popular and effective way for radar remote sensing to extract physical information from the observed scattering for the terrain types [7,10]. There are three CP decomposition algorithms named m − δ decomposition, m − α decomposition and m − χ decomposition [10].…”
Section: Decomposition Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the relationship between field-observed biomass with each metric was first examined using both the linear and exponential regression analyses according to the previous studies [17,48]. These metrics included VIs derived from hyperspectral data and LiDAR-derived metrics.…”
Section: Regression Analysismentioning
confidence: 99%
“…Recently, with the development of remote sensing techniques, different methods have been developed to estimate biomass and yields based on satellite data. One approach develops statistical relationships between the satellite-derived vegetation indices (VIs) and field measured biomass or yields [5][6][7]. These regression models are widely used because they are simpler and more convenient than multivariate statistical methods; nevertheless, they are limited to local applications and are difficult to extend because they lack a theoretical basis.…”
Section: Introductionmentioning
confidence: 99%